Calathea calderon-saenzii (marantaceae), a new attractive patterned-leaved species, endemic to Colombia (2016)
Calathea calderon-saenzii H. Kenn. & M. Serna, endemic to Colombia, is described as new. It is known from the western cordillera of Colombia in the Department of Valle del Cauca and from the eastern cordillera in the departments of Santander and Cundinamarca and occurs in tropical wet to montane cloud forest. It is characterized by the presence of 1-2 cauline and 3-8 basal leaves per shoot; juvenile, and often cauline, leaves patterned with somewhat rectangular yellow-green blotches on a dark green blade; the single inflorescence per shoot of 10-21, remote, spreading green bracts; the absence of bracteoles; and the white sepals. Calathea calderon-saenzii, like the closely related C. elliptica (Roscoe) K. Schum. and C. bantae H. Kenn., has patterned juvenile foliage and an inflorescence of lax, spreading, spirally arranged green bracts but differs in the juvenile leaf pattern of blotches rather than white or pink lines or longitudinal bands of yellow-green, and the absence vs. presence of bracteoles. Calathea calderon-saenzii H. Kenn. & M. Serna, endémica de Colombia, es descrita como especie nueva. Es conocida del occidente de Colombia en el departamento del Valle del Cauca y del oriente en los departamentos de Santander y Cundinamarca y se distribuye desde bosques húmedos y se distribuye desde bosques humedos tropicales, hasta bosques montanos. Se caracteriza por la presencia de 1–2 hojas caulinares y de 3–8 hojas basales por tallo. A menudo las hojas caulinares presentan manchas de color amarillo-verdoso de tipo rectangular sobre el haz verde oscuro. Posee una sola inflorescencia por pianta, con 10–21 brácteas verdes levemente esparcidas, ausencia de bractéolas y sépalos blancos. Calathea calderon-saenzii, como C. elliptica (Roscoe) K. Schum. y C. bantae H. Kenn, exhibe un follaje juvenil y una inflorescencia con brácteas verdes espiraladas, laxas y esparcidas, pero difiere en el diseño de manchas de hojas juveniles de lineas blancas o rosadas de bandas longitudinales amarillo-verdosas y la ausencia versus la presencia de bractéolas